A Novel Approach for the Grid-Serving Implementation of Charging Infrastructures and Their Techno-Economic Integration in the Existing Power Grid - Timo Alexander Hertlein; Ivana Mladenovic; Christian Weindl (Energies)
The integration of electromobility with its required charging infrastructures into the existing power grid, which is demanded by politics and society, is an enormous challenge for electrical power grid operators. Especially considering further challenges, such as the electrification of heat supply systems and sector coupling, it is to be expected that the power grid’s capacity will be strongly overstrained. On the other hand, grid expansion is an extremely expensive and time-consuming method of ensuring that the existing grid is not overloaded, and sufficient grid capacity is available. A suitable grid operations management approach can enable comprehensive and grid-serving control of flexibility, especially charging processes. This article presents a cluster-based and incentive-oriented grid operation management concept and describes the integration of the system into the current German regulatory framework. In addition, the structural integration of charging infrastructures for electromobility into a grid-oriented control system is presented. The suitability of grid charges and their dynamization for stimulating grid-oriented behavior is analyzed. Furthermore, the derivation of additional costs arising from the utilization-dependent thermal aging of grid assets and their imputed integration into the incentive system is described.